2012
DOI: 10.1088/1748-9326/7/1/014024
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spectral nudging on typhoon formation in regional climate models

Abstract: Regional climate models can successfully simulate tropical cyclones and typhoons. This has been shown and was evaluated for hindcast studies of the past few decades. But often global and regional weather phenomena are not simulated at the observed location, or occur too often or seldom even though the regional model is driven by global reanalysis data which constitute a near-realistic state of the global atmosphere. Therefore, several techniques have been developed in order to make the regional model follow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…For the first step of downscaling, 6-hourly reanalysis data were used as the initial and boundary conditions for running the model for a "basic" domain D1 covering the central part of European Russia with a size of approximately 1700 km × 1700 km and a 12-km horizontal grid step, 140 × 140 grid cells ( Figure 1a). In addition, to ensure a more reliable binding of the internal model mode to the real atmospheric dynamics, the spectral nudging technique [52] was applied, which is important for such studies [53,54]. Modeling results for D1 were used as the initial and boundary conditions for intermediate domain D2 with a size of 600 km × 600 km (200 × 200 grid cells) and a 3-km grid spacing covering the Moscow region and the neighboring regions of Russia.…”
Section: Regional Climate Modelmentioning
confidence: 99%
“…For the first step of downscaling, 6-hourly reanalysis data were used as the initial and boundary conditions for running the model for a "basic" domain D1 covering the central part of European Russia with a size of approximately 1700 km × 1700 km and a 12-km horizontal grid step, 140 × 140 grid cells ( Figure 1a). In addition, to ensure a more reliable binding of the internal model mode to the real atmospheric dynamics, the spectral nudging technique [52] was applied, which is important for such studies [53,54]. Modeling results for D1 were used as the initial and boundary conditions for intermediate domain D2 with a size of 600 km × 600 km (200 × 200 grid cells) and a 3-km grid spacing covering the Moscow region and the neighboring regions of Russia.…”
Section: Regional Climate Modelmentioning
confidence: 99%
“…The technique was applied here only for horizontal wind components. It was shown by Feser and Barcikowska (2012) that spectral nudging is very efficient at reducing the RCM's internal variability. Consequently, the simulated large-scale climate was in very good agreement with the driving fields, and the representation of TC climatology significantly improved.…”
Section: Model Set Up and Global Forcing Datamentioning
confidence: 99%
“…This has been achieved with an application of a spectral nudging technique. Feser and Barcikowska (2012) have shown that the technique substantially reduces both the simulated positive bias of the Asian monsoon circulation (e.g. westerly winds, relative vorticity and precipitation) and the negative bias of the subtropical high.…”
Section: Simulated and Observedmentioning
confidence: 99%
“…They showed that the spectrally nudged version of the regional model reproduces the observed polar lows in all the members of the ensemble, reducing significantly the inter-members spread. In a similar study, Feser and Barcikowska (2012) showed that the spectral nudging technique improves the representation of typhoons tracks in the Pacific ocean, reducing some of the biases with respect to the observed best track data.…”
Section: Discussionmentioning
confidence: 93%